2014
DOI: 10.1177/0886260514552445
|View full text |Cite
|
Sign up to set email alerts
|

“Strength at Home” Intervention for Male Veterans Perpetrating Intimate Partner Aggression

Abstract: Veteran and active duty populations evidence higher rates of intimate partner aggression (IPA) than comparable civilian groups, perhaps due in part to their unique service-related experiences. IPA offender treatment programs that take military background into consideration are not widely available, and it is unclear to what extent there is a perceived need for them among clinicians who serve service members and Veterans. Strength at Home (SAH) is a promising 12-session cognitive-behavioral group intervention d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…These factors can also increase risk of suicidal outcomes (Boscarino, 2006; Ilgen et al, 2010c) and therefore could somewhat confound the association between drug problems and suicidal ideation that was discovered in this study. Nevertheless, services that help treat substance abuse and the potential underpinnings of substance abuse might especially benefit young Veteran populations (Chen et al, 2015; Love et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…These factors can also increase risk of suicidal outcomes (Boscarino, 2006; Ilgen et al, 2010c) and therefore could somewhat confound the association between drug problems and suicidal ideation that was discovered in this study. Nevertheless, services that help treat substance abuse and the potential underpinnings of substance abuse might especially benefit young Veteran populations (Chen et al, 2015; Love et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Gallaway and colleagues studied active duty Army soldiers and found that male soldiers reported significantly more minor and severe physical aggression (e.g., throwing something at someone, pushing, shoving, hitting, or, less frequently, using a knife/gun on someone) compared to female soldiers (Gallaway et al 2012 ), whereas an investigation by Afari and colleagues examined self-reported aggression and found that male and female veterans report similar levels of aggressive behavior (Afari et al 2015 ). Another challenge to understanding aggressive behavior in veterans and service members is that research in this area includes individuals with behavioral diagnoses such as intimate partner violence (Tharp et al 2014 ; LaMotte et al 2014 ; Love et al 2014 ; Bradley 2007 ), irritable depression, and PTSD (Campbell et al 2015 ; Flanagan et al 2014 ; Reardon et al 2014 ; Karairmak and Guloglu 2014 ; Angkaw et al 2013 ; Elbogen et al 2013 ). Indeed, the co-occurrence of TBI and PTSD has raised considerable debate in recent years with a number of investigators arguing that the two diagnoses frequently co-occur, however blurred the directionality of the etiology may be (Brenner et al 2010 ; Carlson et al 2011 ; King 2008 ; Morissette et al 2011 ; Shandera-Ochsner et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 details the selection process for included articles, with 13 eligible for inclusion in this review. These articles identified 10 MBCPs: Contexto Program (Carbajosa, Catalá-Miñana, et al, 2017), Domestic Abuse Program (Blatch et al, 2016), Facing Up (Gray, Lewis, et al, 2014), Stopping the Violence (Gray, Broady, Gaffney, Lewis, & Mokany, 2014), Taking Responsibility (Broady, Gray, & Gaffney, 2014; Broady et al, 2015; Gray, Broady, Gaffney, & Lewis, 2015; Gray, Broady, Gaffney, Lewis, & Mokany, 2014; Gray, Lewis et al, 2014), Group Cognitive-Behavioral Therapy (Semiatin et al, 2013), High-Intensity Family Violence Prevention Program (HIFVPP) (Connors et al, 2013), REAL Fathers Initiative (Ashburn et al, 2017), Standard Batterer Intervention Program (Lila et al, 2018), and Strength at Home (SAH; Love et al, 2015). The final report for Project Mirabal—DVPP is included here; however, specific DVPP details were not included in this report (Kelly & Westmarland, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Of all the articles, six articles evaluate Australian MBCPs (Blatch et al, 2016; Broady, Gray, & Gaffney, 2014; Broady, Gray, Gaffney, & Lewis, 2015; Gray, Broady, Gaffney, & Lewis, 2015; Gray, Broady, Gaffney, Lewis, & Mokany, 2014; Gray, Lewis, et al, 2014), two articles evaluate US MBCPs (Love et al, 2015; Semiatin et al, 2013), two articles evaluate MBCPs in Spain (Carbajosa, Catalá-Miñana, et al, 2017; Lila et al, 2018), and the remaining three articles individually evaluate MBCPs in the United Kingdom (Kelly & Westmarland, 2015), Canada (Connors et al, 2013), and Uganda (Ashburn et al, 2017). Of the 10 interventions, 7 describe the theoretical approaches and models to support the programs, including motivational interviewing (Lila et al, 2018; Semiatin et al, 2013), cognitive and behavioral psychology (Blatch et al, 2016; Carbajosa, Catalá-Miñana, et al, 2017; Love et al, 2015; Semiatin et al, 2013), risk-need-responsivity (Blatch et al, 2016; Connors et al, 2013), social cognitive theory (Ashburn et al, 2017), social learning theory (Ashburn et al, 2017), and theory of change (Ashburn et al, 2017). Three interventions (Facing Up, Stopping the Violence, and Taking Responsibility) do not specify the theoretical approaches used to underpin the programs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation